Development of a battery electric vehicle sector in North-West Europe: challenges and strategies. (2013) - Özel, Fatih Mehmet; Ernst, Christian-Simon; Davies, Huw C.; Eckstein, Lutz
Electric propulsion is a technological alternative to the internal combustion engine. However, the transition to electric propulsion represents a considerable challenge. The European Network on Electric Vehicles and Transferring Expertise (ENEVATE) has undertaken an analysis of the supply chain for the Battery Electric Vehicle (BEV) in North-West Europe to identify the challenges and develop strategies for a strong BEV sector. A production structure analysis, make or buy analysis, value-add analysis, white spot analysis and competitor analysis were conducted in that context. It was found that North-West Europe has a good potential for the development of a healthy BEV sector owing to its innovative automotive industry, strong financial background, flexible production lines and skilled workers. However, without improvements in the level of BEV production, Research and Development (R&D) investments, infrastructure and market share, these advantages are not necessarily sufficient for the region to be a leader in the global BEV industry.